Peningkatan Overall Equipment Effectiveness (OEE) dengan Pendekatan Total Productive Maintenance (TPM) di Line X PT Kraft Ultrajaya Indonesia - Faizal Agni Akbar; Aviasti (UNISBA Press, 2023)
Abstract. PT Kraft Ultrajaya Indonesia is a manufacturing company specializing in cheese processing. PT Kraft Ultrajaya Indonesia has started to produce cheese in 1994 with a continuous production system (Contionous Process) which produces large-scale products, by using Cheese Cutter machines, Grinder machines, machines, Cookers, Filling machines, Cooling Tunel machines, and Packing. Based on data for November 2021, Line X has a high downtime of 4,840 minutes. Therefore, the focus of this research is only to reduce downtime on line X by focusing on the preventive maintenance, autonomous maintenance, and quality maintenance pillars on the Total Productive Maintenance (TPM) pillar.Based on the data processing that has been done, line X has an average value of Overall Equipment Effectiveness (OEE) of 83%. This value still does not meet the standard set by the Japan Institute of Plan Maintenance (JIPM) which is 85%. The OEE value is improved by considering the Six Big Losses. Based on the calculation, the loss factors that affect the OEE line X value are Idling and Minor Stoppage with a percentage of 8%, Setup and Adjustment with a percentage of 5%, Defect Amount with a percentage of 4%.Proposed improvements are made by focusing on the three pillars of Total Productive Maintenance (TPM), namely preventive maintenance, autonomous maintenance, and quality maintenance. The pillars of preventive maintenance and autonomous maintenance are carried out by making maintenance schedules, namely CIL (Cleaning, Inspection, and Lubrication), Centerlining which aims to determine the appropriate and standardized machine settings so that they do not change, OPL (One Point Lesson) which is an instruction or stage in carrying out an engine and engine repair. Meanwhile, the quality maintenance pillar is carried out by instructing the operator to be able to check the product every two hours to avoid defective products. The implementation of CIL and OPL to increase the Performance value from 92% to 95%, Quality ratio from 95% to 96%, and increase OEE from 83% to 86%. Abstrak. PT Kraft Ultrajaya Indonesia merupakan perusahaan manufaktur yang mengkhususkan diri dalam bidang pengolahan keju. PT Kraft Ultrajaya Indonesia sudah mulai melakukan produksi keju pada tahun 1994 dengan sistem produksi secara berkelanjutan (Contionous Process) yang memproduksi produk berskala besar, dengan pengerjaannya menggunakan mesin Cheese Cutter, mesin Grinder, mesin, Cooker, mesin Filling, mesin Cooling Tunel, dan Packing. Berdasarkan data bulan November 2021, Line X memiliki downtime yang tinggi yaitu 4.840 menit. Oleh karena itu fokus penelitian ini hanya untuk mereduksi downtime pada line X dengan memfokuskan pada pilar preventive maintenance, autonomous maintenance, dan quality maintenance pada pilar Total Productive Maintenance (TPM).Berdasarkan pengolahan data yang telah dilakukan, line X memiliki nilai rata – rata Overall Equipment Effectiveness (OEE) sebesar 83%. Nilai tersebut masih belum memenuhi standar yang telah ditetapkan oleh Japan institute of Plan Maintenance (JIPM) yaitu 85%. Nilai OEE diperbaiki dengan mempertimbangkan Six Big Losses. Berdasarkan perhitungan, faktor kerugian yang mempengaruhi nilai OEE line X adalah Idling and Minor Stoppage dengan persentase 8%, Setup and Adjusment dengan persentase 5%, Defect Amount dengan persentase 4%.Usulan perbaikan dilakukan dengan berfokus menggunakan tiga pilar Total Productive Maintenance (TPM), yaitu preventive maintenance, autonomous maintenance, dan quality maintenance. Pilar preventive maintenance dan autonomous maintenance dilakukan dengan membuat penjadwalan pemeliharaan yaitu CIL (Cleaning, Inspection, dan Lubrication), Centerlining yang berutujuan untuk menentukan setting mesin yang sesuai dan distandarisasi agar tidak berubah, OPL (One Point Lesson) yaitu sebuah intruksi atau tahapan dalam menjalankan sebuah mesin dan perbaikan mesin. Sementara itu pilar quality maintenance dilakukan dengan menginstuksikan operator untuk dapat melakukan pengecekan produk setiap dua jam sekali untuk menghindari adanya produk yang cacat. Penerapan CIL dan OPL dapat meningkatkan nilai Performance dari 92% menjadi 95%, Quality ratio dari 95% menjadi 96%, dan meningkatkan OEE dari 83% menjadi 86%.